2022
DOI: 10.18844/cjes.v17i9.8002
|View full text |Cite
|
Sign up to set email alerts
|

Increasing students’ culture literacy using virtual reality field trip model: Need analysis

Abstract: The rapid exchange of information through technology has caused a cultural change in Indonesia. This causes the local culture to be lost and the penetration of foreign cultures. This article aimed to analyze the need to develop Field Trip Model Virtual Reality for elementary school students. This study used the qualitative descriptive method. The 50 students and 28 teachers from an elementary school in Jakarta became participants.  The data were collected using questionnaires form and interviews. The data were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 37 publications
1
4
0
1
Order By: Relevance
“…Some teachers use lecture and presentation methods in teaching culture, causing students to be uninterested in culture, even if only briefly. This is in line with the results of research whose authors reported that students' interest in learning local culture is still low [26], [27], [28].…”
Section: Students' Interest Level Towards Cultural Learningsupporting
confidence: 90%
“…Some teachers use lecture and presentation methods in teaching culture, causing students to be uninterested in culture, even if only briefly. This is in line with the results of research whose authors reported that students' interest in learning local culture is still low [26], [27], [28].…”
Section: Students' Interest Level Towards Cultural Learningsupporting
confidence: 90%
“…Everyone has a different understanding of conveying health issues; therefore, a person's behavior or personality can affect the understanding of coronavirus information. Health communication aims to increase human resources' quality through several educational and training efforts to increase knowledge and shape communication attitudes and behavior (Iasha et al, 2022;Koltay, 2011). This communication behavior is not only direct but also through social media.…”
Section: Resultsmentioning
confidence: 99%
“…This research adopted a qualitative descriptive research method concerned with identifying the findings without data manipulation or other types of treatment. Qualitative descriptive research is a research method that utilizes qualitative data, is described descriptively, and is often used to analyze events, phenomena, or social circumstances (Iasha et al, 2022;Trifena Tarusu et al, 2022). Qualitative descriptive research is a combination of descriptive and qualitative research.…”
Section: Research Modelmentioning
confidence: 99%